PROBLEM ISSUES OF MILITARY SERVICE IN THE CONTEXT OF IMPLEMENTING THE CONSTITUTIONAL DUTY TO DEFEND THE HOMELAND - Piskun, Ivan; Chunakov, Roman (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose: to analyze the current state of administrative and legal regulation of some issues of military service in Ukraine. To investigate the main changes in national legislation in the context of implementing the constitutional duty of citizens of Ukraine to defend the Fatherland. Research methods: the research method was the formal-legal method, through which the analysis of the current legislation of Ukraine and local regulatory legal acts in the field of administrative and legal regulation of a separate type of military service in Ukraine was carried out, and the method of statistical research, through which the collection, processing and analysis of information was carried out. The results: an analysis of the dynamics of changes in the Law of Ukraine “On Military Duty and Military Service” was carried out, which indicates an attempt to solve the current problems faced by the legislator. However, such frequent legislative amendments gradually create a risk of imbalance in the system, which complicates its effective functioning and implementation of the established norms. It is noted that it is advisable to systematically and systematically train citizens in the context of fulfilling the constitutional obligation during basic military service. In particular, it is proposed to systematize the completion of basic military service by citizens who have received a certain degree of education, provided that they have not continued their studies.